A STUDY OF THIOPENTAL SODIUM-INDUCED SLEEP IN WISTAR RATS IN DOSES OF QUININE AND ARTESUNATE - B, Ezenwanne E; Onobu, Abuda (Pakistan Journal of Physiology, 2018)
Background: Full knowledge of the actual central nervous system properties of both quinine and artesunate is still hazy and far from very clear. There are no scientific data to support the suggestion that either of these drugs possess properties that modify the functioning of central nervous system. It was the aim of this study to evaluate the patterns of thiopental sodium-induced sleep in separately administered doses of quinine and artesunate in Wistar rats. Method: Healthy adult rats of comparable size, weight and age were employed to examine the onset time (latency) and duration of thiopental sodium-induced sleep in separate pretreated doses of quinine and artesunate. The time of the Onset and Duration of the induced sleep were computed in varying doses of each of the drugs. The results were expressed as Mean±SEM, and values of p≤0.05 were regarded as statistically significant. Results: The onset time of the induced sleep were significantly decreased in higher doses of quinine (p≤0.05) while the sleep duration were prolonged (p≤0.05; p≤0.01) in higher doses of both drugs, indicative that the animals sleep quicker with corresponding longer sleeping time in high doses in both quinine and artesunate. Conclusion: Both quinine and artesunate possess some central properties that account for the observed potentiating influence on the induced sleep. The promoting effects on the induced sleep may be linked to serotonergic mechanism or the GABA mechanism in the brain. Pak J Physiol 2018;14(1):10–2